Examining the validity of the polish short form version of the self-regulated learning—sport practice survey among competitive athletes - Siekanska, Malgorzata; Wilson, Stuart G.; Blecharz, Jan; Young, Bradley W. (Frontiers in Psychology, 2023)
Self-regulated learning entails psychological processes that elite athletes employ to optimize their practice (McCardle et al., 2019). Although self-regulated learning provides insights into athlete-led practice, research has been limited to few cultures, and the particularities of how SRL surveys perform in new cultural contexts requires attention. Moreover, there exists no measure to assess SRL and its relationship to quality sport practice in Polish. Thus, we examined the Short Form of the Self-Regulated Learning ¬¬– Sport Practice (Wilson et al., 2019) survey in Polish. Analyses addressed the factorial validity and reliability, the criterion validity (by assessing differences in scores between competition levels), and the concurrent validity (by correlating scores with conceptually related constructs) of a Polish Short Form survey. Athletes (N = 324, Mage=21.4, nfemales=144, nmales=180) from amateur, regional, national, and international-elite levels completed the survey, along with concurrent subscales (General Self-Efficacy Scale; GSES; Metacognitive-Self Scale; MS-24; Action Control Scale; ACS-90). Confirmatory factor analysis indicated a two-factor (metacognitive; motivational) model (RMSEA=.082, SRMR=.057, CFI=.89). Between-group tests showed international-elite scoring higher than all other groups on metacognitive and motivational subscales. On both subscales, significant trends indicated that more skilled levels consistently reported higher scores than lesser skilled levels. The short form scores were associated with certain concurrent variables, including GSES (rmeta=.41, rmotiv=.48), MS-24 (rmeta=.39, rmotiv=.24), and ACS-90 (AOF subscale: rmotiv=.26). On the basis of strong criterion validity, and moderate evidence for concurrent validity, we conclude that the Polish Short Form of the Self-Regulated Learning – Sport Practice survey is a promising tool for use in Polish sport and we discuss future avenues of work to enhance its validation. Limitations that inform future research include our reliance on a mixed-sport sample, the lack of priming of obstacles/challenge ahead of self-report, and a lack of consideration of sport-specific practice variables in analyses.